2010
DOI: 10.2471/blt.08.058230
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of skin-barrier-enhancing emollients among preterm infants in Bangladesh

Abstract: Objective To evaluate the cost-effectiveness of topical emollients, sunflower seed oil (SSO) and synthetic Aquaphor, versus no treatment, in preventing mortality among hospitalized preterm infants (< 33 weeks gestation) at a tertiary hospital in Bangladesh. Methods Evidence from a randomized controlled efficacy trial was evaluated using standard Monte Carlo simulation. Programme costs were obtained from a retrospective review of activities. Patient costs were collected from patient records. Health outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The trial demonstrated the lifesaving potential of emollient use and its cost effectiveness. The incremental cost to achieve these results was US$2.15 per year of life lost averted and US$61.00 per death averted, making it one of the most cost-effective interventions available 26. A hospital-based study in India also showed significantly greater mean daily weight gain (2.54 g, 95% CI 1.33 g to 3.75 g) among preterm infants receiving emollient therapy with CO compared with mineral oil 19.…”
Section: Discussionmentioning
confidence: 99%
“…The trial demonstrated the lifesaving potential of emollient use and its cost effectiveness. The incremental cost to achieve these results was US$2.15 per year of life lost averted and US$61.00 per death averted, making it one of the most cost-effective interventions available 26. A hospital-based study in India also showed significantly greater mean daily weight gain (2.54 g, 95% CI 1.33 g to 3.75 g) among preterm infants receiving emollient therapy with CO compared with mineral oil 19.…”
Section: Discussionmentioning
confidence: 99%
“…69 In randomized, controlled trials in hospitals in Egypt and Bangladesh, sunflower seed oil applications reduced the incidence of neonatal sepsis by about 40 to 50%, 5,81 and in Bangladesh they reduced the risk of mortality by 26%. 82 Thus, evidence exists to promote the use of this highly cost effective intervention 102 in hospitalized, preterm infants <33 weeks gestational age in low resource settings. However, further research is needed on the impact of this intervention in all newborns (that is, both term and preterm infants) in the hospital, and no data exist on the impact of this intervention in community settings.…”
Section: Topical Agents and Oil Massagementioning
confidence: 99%
“…In a randomized study of 497 preterm neonates in Bangladesh, thrice-daily topical application of sunflower seed oil significantly reduced sepsis and mortality rates by 41 and 26 %, respectively, both significantly higher than the untreated control [14,15]. In reducing sepsis rates, sunflower seed oil actually slightly outperformed a petroleum-based emollient and at a vastly lower cost [16]. These studies support a possible role for sunflower seed oil in treating diseases of skin-barrier dysfunction, including atopic dermatitis.…”
Section: Sunflower Seed Oilmentioning
confidence: 89%